Macroeconomic variables and banking sector development: Evidence from Nigeria - Adelakun, Ojo Johnson; Afolabi, Babatunde; Abuh, Uwasejike B (Technium Social Sciences Journal, 2020)
The study assessed the relationship between Macroeconomic Variables and Development in the Nigerian Banking Sector using annual time series data. Models were specified using Ratio of Credits to Private Sector to Gross Domestic Product (GDP) as a proxy for Banking Sector Development. At the same time, GDP growth rate, Poverty, Exchange Rate, Oil Price, Poverty, Money Supply, Inflation, and Interest rates were the selected Macroeconomic Variables used in the study. Data used were sourced from the Statistical Bulletin of Central Bank of Nigeria (CBN) for various editions and estimated using ARDL Bound Test and Vector Error Correction Mechanism (VECM). The study found that there exists a long-run relationship between Macroeconomic Variables selected and Banking Sector Development. The VECM coefficients revealed that all variables except Interest Rates have negative effects on Banking Sector Development. The VECM (-1), which showed the speed of adjustment, was rightly signed and significant, indicating a long-run causality relationship running from macroeconomic variables to banking sector development. The Impulse response from restricted VAR revealed that Banking Sector responded to the Macroeconomic Variables of which GDPGR and INT were transmitting negatively to Banking Sector Development while others were transmitting positive impulses. However, the variance decomposition found that oil price, followed by GDPGR and poverty, caused more variation in Banking Sector Development. In contrast, inflation and money supply caused the least variation in Banking Sector Development. The study, therefore, concluded that selected Macroeconomic Variables have a significant long-run relationship with Banking Sector Development. It is therefore recommended, among others that, Macroeconomic indicators should be well monitored and controlled using macroeconomic instruments promptly since when they are well managed would lead to a better developed Banking Sector in Nigeria.